2012
DOI: 10.1111/j.1439-0310.2012.02037.x
|View full text |Cite
|
Sign up to set email alerts
|

Display Behavior and Habitat Use in Single and Mixed Populations of Anolis carolinensis and Anolis sagrei Lizards

Abstract: Introduced species can have a variety of effects on the behavior and ecology of native species. We compared display behavior and habitat use of introduced Anolis sagrei and native Anolis carolinensis lizards across three sites in Southern Louisiana. The chosen sites were similar in that they were all located in urban settings with clumped vegetation. The first site contained only A. sagrei, the second supported sympatric A. sagrei and A. carolinensis populations, and the third site harbored only A. carolinensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…Closely related and morphologically similar to high-perching trunkcrown anoles in Cuba (Williams, 1969;Glor et al, 2005;Campbell-Staton et al, 2012), A. carolinensis perches at low heights in the absence of other Anolis lizards but shifts to higher perches in the presence of the larger, also low-perching A. sagrei (Collette, 1961;Edwards and Lailvaux, 2012;Stuart et al, 2014). In this study, we assess the effect of the presence of A. sagrei on the movement rates of male and female A. carolinensis by comparing populations of A. carolinensis where they are the only anoles present to populations of A. carolinensis where they cooccur with A. sagrei.…”
Section: Introductionmentioning
confidence: 97%
“…Closely related and morphologically similar to high-perching trunkcrown anoles in Cuba (Williams, 1969;Glor et al, 2005;Campbell-Staton et al, 2012), A. carolinensis perches at low heights in the absence of other Anolis lizards but shifts to higher perches in the presence of the larger, also low-perching A. sagrei (Collette, 1961;Edwards and Lailvaux, 2012;Stuart et al, 2014). In this study, we assess the effect of the presence of A. sagrei on the movement rates of male and female A. carolinensis by comparing populations of A. carolinensis where they are the only anoles present to populations of A. carolinensis where they cooccur with A. sagrei.…”
Section: Introductionmentioning
confidence: 97%
“…These displays have been extensively studied in green anoles (e.g., Jenssen et al. ; Lovern and Jenssen ; Bloch and Irschick ; Edwards and Lailvaux ) and occur with significantly higher frequency in the breeding season compared to the nonbreeding season (Jenssen et al. , ).…”
Section: Introductionmentioning
confidence: 99%
“…Male green anoles extend their dewlaps in combination with headbobs and pushups to form stereotyped sequences of visual displays that are used in a variety of ecological contexts, including courtship displays to females and aggressive displays to other males (Decourcy and Jenssen 1994). These displays have been extensively studied in green anoles (e.g., Jenssen et al 2000;Lovern and Jenssen 2003;Bloch and Irschick 2006;Edwards and Lailvaux 2012) and occur with significantly higher frequency in the breeding season compared to the nonbreeding season (Jenssen et al 1995(Jenssen et al , 2001. Irschick et al (2006) observed that male green anole dewlaps change size between the breeding and nonbreeding seasons in nature, being larger in the summer when anoles are actively breeding as compared to in the spring and winter.…”
Section: Introductionmentioning
confidence: 99%
“…However, when A. sagrei is introduced into an environment previously dominated by A. carolinensis , A. carolinensis commonly exhibits shifts in habitat use and often becomes rarer within a period of a few years (Echternacht, ; Campbell, ). Indeed, several studies, including a recent study of anoles in New Orleans, have found that A. carolinensis perches significantly higher when A. sagrei are present, suggesting that A. sagrei are actively displacing the native green anoles (Collette, ; Losos & Spiller, ; Edwards & Lailvaux, ). The factors behind this shift in habitat are currently unclear, but the population in New Orleans offers an ideal study situation to address this question.…”
Section: Introductionmentioning
confidence: 99%